Ethnochemistry: Exploring the Silk Ecoprint Steaming of Kampung Sabbeta as a Source of Learning Chemistry - Nur Yusaerah; Novia Anugra; Desy Anwar; Nurfadillah Nurfadillah (Hydrogen: Jurnal Kependidikan Kimia, 2023)
Kampung Sabbeta is one of the community empowerment locations that is developing ecoprint techniques for natural materials as fabric dyes and eco-friendly motif printers in Soppeng Regency, South Sulawesi Province. Considering the importance of knowledge about the environment, it is necessary to provide environmental management using natural materials as an effort to foster awareness of learning that is integrated with local wisdom values. This research was carried out to reveal the chemical aspects contained in the process of making steamed ecoprint fabric starting from the scouring, mordanting, ecoprinting, steaming and fixation processes which can be used as a resource for learning chemistry. The aim of this research is to reveal the chemical aspects and fundamental chemical activities contained in the silk steaming ecoprint process in Kampung Sabbeta. This research uses a type of qualitative descriptive with ethnographic methods, observation, interviews, and documentation. Data analysis in this research uses source triangulation which was carried out inductively, so that in this study key informants, main informants and supporting informants were determined in each aspect that became the object of research. The results show that the fundamental activities involved in the process of making silk ecoprint steaming in Kampung Sabbeta include formulating, measuring, purifying, fabricating, and playing. The chemical concepts that can be uncovered are solution preparation, purification, unit conversion in chemistry, adsorption, natural oxidation reactions, heat transfer.